Metode Coaching Berpendekatan IASP Sebagai Upaya Pelayanan Pembimbingan Akademik Mahasiswa PGSD Stahn Mpu Kuturan - I Ketut Ngurah Ardiawan (STAHN Mpu Kuturan Singaraja, 2022)
The role of lecturers in carrying out their main tasks, apart from the Tri Dharma of Higher Education, namely education, research and community service, also provides academic guidance services to students. Coaching with an IASP approach is a method to inspire an individual's creative thinking so that he can maximize his personal and professional potential with the help of video conferencing media, be it through the Zoom application, Google Meet or others. The stages of this method are Identification, helping to see/identify what is actually in the situation; Appreciation, is a form of giving awards and assessments; and Solution, together students look for creative solutions to a problem. With the strategy of providing academic guidance services using the coaching method with an IASP approach, it is hoped that there will be collaboration between students and lecturers by finding the best solution in the mentoring process to improve academic achievement while students are studying at STAH Negeri Mpu Kuturan Singaraja.